The determinants of MNE subsidiaries' political strategies: evidence of institutional duality - Hillman, Amy J; Wan, William P (Journal of International Business Studies, 2005)
In this study, we develop and test a model of the determinants of political strategies used by foreign subsidiaries of multinational enterprises (MNEs). Using recent theoretical advances in institutional theory that recognize that MNE subsidiaries are confronted with pressures for isomorphism within the corporation (internal legitimacy) and within the host country (external legitimacy), we integrate international business and political strategy literatures to create a multilevel model of subsidiary, host country and parent determinants of political strategy. Our hypotheses are tested using survey and archival data from Western European subsidiaries of US MNEs.